Pembagian Harta Waris dalam Masyarakat Nagari Bayua - Dodi Syaputra (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2020)
The purpose of this article is to seek how to distribute inheritance to the people of Nagari Bayua, Tanjung Raya District, Agam Regency. This research is field research using empirical legal research methods by using qualitative methods through interviews with religious leaders, community leaders, and local Pangulu (Indigenous Chief) who understand the distribution of inheritance (livelihoods) to the Nagari Bayua indigenous people. The results shows that the inheritance obtained from parents is divided into heirs according to Islamic law, but customary law is more dominantly used by the Minangkabau people, especially in Nagari Bayua. The people in Nagari have their own way of distributing inheritance by dividing from the oldest child to his younger siblings, and the men do not get any of the inheritance.